A ESCOLA COMO ESPAÇO DE DIÁLOGO: O DESAFIO DO PLURALISMO RELIGIOSO PARA O ENSINO RELIGIOSO - BALEEIRO, Lilian Araújo (2015)
With this thesis we present the inter-religious dialogue, from the Brazilian religious pluralist situation, as a challenge for the discussion of religious education in public schools in the secular state of Brazil, with the purpose to overcome intolerance and religious exclusivism. In the first chapter we will introduce the present situation of religious education, especially in its important historical moments, the relationship with the secular state and the position of the Permanent National Forum of Religious Education (FONAPER). In the second chapter we analyze the Brazilian religious plurality taking into account the elements of the Brazilian religious map, relating it to data from the last census of IBGE, with the intention of knowing the Brazilian religious framework and the plural context in which religious education is inserted. In the last chapter we will discuss a proposal of a religious education as ‘a space of dialogue’ between different religions, making use of the foundational elements of the theology of religious pluralism and interreligious dialogue. The practice of religious education as ‘a space of dialogue’ is brought forward as the option that enables tolerance among religious groups represented in the school environment.